Identification and evaluation of potential tourism area based on landforms in Jeli district, Kelantan - Nor Arina Mohammad Aris (2012)
Jeli is one the district in Kelantan that still keep most of its wilderness area. This research proves that Jeli is rich with natural tourism sources that are preserved until now. This is due to lack of exposure on existence of tourism sites to people outside Jeli and Kelantan. Among of interesting places in Jeli are cave, waterfall, lake, hot spring and cascade. Six locations were identified as study area. Methods that applied in completing this research are on-site observation a checklist approach supported with Likert Scale measurement based on study done by Priskin (2001) which questionnaire distribution. Foremost,type of landforms in Jeli was determined using a geomorphology classification system developed by Haskins et al,..(1998). Thus, findings show that a large part of tourism sites studied is still in good quality such as Pergau Lake, Lata Chenai and others. However, many infrastructures provided are not being well-cared thus impaired the aesthetic value of that particular area. From questionnaire, it is found that visitors that are mostly local people, accept tourism activities in that district because it foster development process such as encouragement in infrastructure, telecommunication and road.